Product Development and Brand Image Effect on Customer Satisfaction in KFC BSD Serpong Branch - Budiyanto, Arief (Jurnal Office, 2019)
This study aims to determine product development and brand image on consumer satisfaction at KFC BSD Serpong Branch. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. This study's results show product development significantly affects consumer satisfaction by 41.3%; the hypothesis test obtained t count> t table or (8,047> 1,985). Brand image has a significant effect on customer satisfaction by 36.8%; hypothesis testing obtained t count> t table or (7,320> 1,985). Product development and brand image simultaneously have a significant effect on consumer satisfaction with the regression equation Y = 10.370 + 0.404X1 + 0.338X2 and the influence contribution is 49.7%, the hypothesis test obtained F count> F table or (44.882> 2,700).